DETERMINAN POLA KONSUMSI PANGAN DAN NONPANGAN RUMAH TANGGA MASYARAKAT MUSLIM DKI JAKARTA PADA MASA PANDEMI COVID-19 - Farhan Baihakki (2023)
Changes in DKI Jakarta consumption patterns the number of food commodities decreased in 2019 to 2020, but increase was in non-food commodities, then morbidity rate, the increase in the number of households, and the burden of dependents that increased became a phenomenon of changing patterns. Consumtion during the COVID-19 pandemic. This study amis to explain the determinants of household consumption patterns in the perspective of islamic economics during the COVID-19 pandemic. The Population in the study was the people of DKI Jakarta. The sample was taken by non-probability sampling with the purposive sampling of this study totaling 180 respondents. The approach used is quantitative. Data collection techniques using a questionnaire. The data analysis technique uses the PLS. The data test uses the outer model, namely convergent a discriminant validity, and cobranch alpha reliability. The inner model testing is the coefficient of determination, model fit, and q-square. Hypothesis testing used or the name t-test. The results of the hypothesis test are that income has a positive effect on food and non-food consumption patterns, the number of family dependents has a positive effect on food and non-food consumption patterns, and lifestyle has a negative effect on food and non-food consumption patterns.